Numerical study of the mixture formation and stratified-flame-induced auto-ignition (SFI) combustion processes in a poppet-valve two-stroke direct injection gasoline engine. (April 2019) - He, Bang-Quan; Lin, Chang-Lin; Li, Xiao; Wang, Xinyan; Zhao, Hua; Zhang, Yan
Highlights: More fuel tends to distribute around spark plug with increased engine speed. Increased engine speed slows down flame propagation with high exhaust dilution. The mass of OH radical in the cylinder can evaluate the occurrence of auto-ignition. High temperature in the peripheral zone facilitates auto-ignition. The fraction of heat released by auto-ignition is higher at high engine speed. Abstract: Two-stroke gasoline engines, as the substitutes of their four-stroke downsized counterparts, can mitigate knock, excessive thermal and mechanical loads for the improvement of fuel economy. But the combustion instability of the two-stroke gasoline engines at low loads is a dilemma. Flame propagation initiated by spark ignition combined with the auto-ignition of the mixture with high residual gas fraction during flame propagation, i.e., stratified-flame-induced auto-ignition (SFI) combustion, is one possible solution to control ignition timing and improve combustion stability of a two-stroke direct injection spark ignition gasoline engine at low loads. To understand the relationships between the mixture formation and SFI combustion event, simulation was conducted at a fixed amount of fuel burned in a cycle. The results show that engine speed affects flame propagation and auto-ignition in the cylinder through the change in the distribution of fuel and residual gases. SFI combustion can occur during flame propagation at different engine speeds. With the increase of engine speed, increased fuel moves towards the spark plug while the temperature of the mixture around the cylinder increases with residual gases, leading to increased heat released by SFI auto-ignition. Although increased engine speed leads to a delay in ignition timing, shortened combustion duration increases indicated mean effective pressure.